An overview on the role of bioactive α-glucosidase inhibitors in ameliorating diabetic complications. (November 2020) - Hossain, Uday; Das, Abhishek Kumar; Ghosh, Sumit; Sil, Parames C.
Abstract: Recently the use of bioactive α-glucosidase inhibitors for the treatment of diabetes have been proven to be the most efficient remedy for controlling postprandial hyperglycemia and its detrimental physiological complications, especially in type 2 diabetes. The carbohydrate hydrolysing enzyme, α-glucosidase, is generally competitively inhibited by the α-glucosidase inhibitors and results in the delayed glucose absorption in small intestine, ultimately controlling the postprandial hyperglycemia. Here we have reviewed the most recent updates in the bioactive α-glucosidase inhibitors category. This review provides an overview of the α-glucosidase inhibitory potentials and efficiency of controlling postprandial hyperglycemia of various bioactive compounds such as flavonoids, phenolic compound, polysaccharide, betulinic acid, tannins, anthocyanins, steroids, polyol, polyphenols, galangin, procyanidins, hydroxyl-α-sanshool, hydroxyl-β-sanshool, erythritol, ganomycin, caffeoylquinic acid, resin glycosides, saponins, avicularin, oleanolic acids, urasolic acid, ethanolic extracts etc., from various dietary and non-dietary naturally occurring sources. Highlights: α-glucosidase inhibitors delay glucose absorption in small intestine. Various α-glucosidase inhibitors from dietary and non-dietary sources have been reported. α-glucosidase inhibitors control postprandial hyperglycemia. 4. AGIs delay polysaccharide digestion to activate GLP1 which stimulates insulin secretion. AGIs exhibit competitive inhibition and diminish carbohydrate hydrolysis.